Pengaruh Karakteristik Perusahaan dan Tingkat Utang terhadap Tax Avoidance - Dwita, Marviana Nur; Zenabia, Tsarina (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to empirically examine the effect of company characteristics and leverage on tax avoidance in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The research method employed is quantitative with an associative approach in a causal relationship. Secondary data obtained from company financial reports were used in this study. The sample was selected using the purposive sampling method, resulting in 17 companies observed over five years. Data analysis was conducted using panel data regression with the assistance of E-Views 12 software. The results indicate that, simultaneously, company characteristics and leverage have a significant effect on tax avoidance. However, partially, company characteristics do not affect tax avoidance, nor does leverage. This study has several limitations, including the sample scope, which only covers one industrial sector over a five-year observation period, and the limited independent variables used, as there are other factors that may influence tax avoidance. Additionally, data collection constraints were encountered due to some companies not fully disclosing their financial statements each year.